Evaluation on Energy Efficiency of Flexible MF-OTP-based EONs in Serving Asymmetric Traffic - Kim, Geunsoo; Kim, Jaehoon; Peng, Limei (Asia Communications and Photonics Conference, ACP, 2018)
In this paper, we evaluated energy efficiency for EONs based on the node architecture using flexible multi-flow optical transponders (MF-OTP) that we have proposed. The proposed MF-OTP architecture can flexibly set respective sub-channel's transmission direction to be either upstream or downstream and decide flexible modulation format for each sub-channel, which therefore allows to efficiently transmit asymmetric traffic. With such flexible transmission architecture, we design and evaluate an integer linear programming (ILP) model to optimize the power consumption with considerations on the routing, modulation, spectrum assignment (RMSA). The goal of the ILP model is to find the optimal value for the required number of sub-channels used and the subsequent power consumption.
Keywords: Asymmetric traffic; Flexible transmissions; Integer linear programming models; MF-OTP; Modulation formats; Node architectures; Optical transponders; Spectrum assignment; MF-OTP; Power Consumption; Traffic Asymmetric